Nutrient solubilization and its availability following anaerobic digestion. - Mehta, Chirag M. (Water Science and Technology)
This study aims to investigate solubilization of elements (P, N, K, Ca and Mg) during anaerobic digestion (AD) of solid agriculture waste. It is important to maintain particularly phosphorous in the aqueous phase to be able to subsequently recover it in a concentrated form via crystallization. Batch AD was carried out at a mesophilic condition (37 °C) and pH 7.0 ± 0.2 on a variety of piggery and poultry solid waste streams. Less than 10% of the total P, Ca and Mg was in soluble form in the digestate. Most of the N and K remained soluble in the digestate. A bioavailability test (citric acid extraction) showed P, Ca and Mg in the digestate were totally available. Complete solubilization of P, Ca and Mg occurred below a threshold of pH 5.5. This indicates these nutrients were released during digestion, and then either bound to form inorganic compounds or adsorbed on solid surfaces in the digestate. These effects reduce the feasibility of post-digestion recovery of the nutrients via struvite crystallization. Strategies to improve nutrient solubilization and recovery during the AD include addition of complexing chemicals, operation at depressed pH, or otherwise modifying the operating conditions.